2011
DOI: 10.4018/jksr.2011010103
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Virtual World Environments in Student Satisfaction

Abstract: Universities and educational institutions worldwide are currently becoming more dependent on delivering assorted courses within online virtual worlds as 3D Virtual Learning Environments (3D VLES

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Despite its relevance in autonomous learning and the skills of future engineers and designers, the enhancement of these qualities by virtual learning environments is not sufficiently contrasted. In fact, most of the work focuses on assessing the quality of immersion and interaction with the environment, as well as the comfort of use [23]. Aspects such as fostering imagination and creativity are often overshadowed, especially as they are particularly difficult to measure objectively [24].…”
Section: Introductionmentioning
confidence: 99%
“…Despite its relevance in autonomous learning and the skills of future engineers and designers, the enhancement of these qualities by virtual learning environments is not sufficiently contrasted. In fact, most of the work focuses on assessing the quality of immersion and interaction with the environment, as well as the comfort of use [23]. Aspects such as fostering imagination and creativity are often overshadowed, especially as they are particularly difficult to measure objectively [24].…”
Section: Introductionmentioning
confidence: 99%
“…Virtual reality technology, as can be seen in Fig. 7, is applied more for training environments such as maintenance of aircraft, information technology equipment and manufacturing products, which can be seen as useful and with potential, due to the possibility to design learning applications with visualization to learn complex technical maintenance processes [17]. No research in Further Education (FE) was found where any of the technologies were applied.…”
Section: Application Of Mixed Reality To Educationmentioning
confidence: 99%
“…Despite its relevance in autonomous learning and in the capacities of future engineers and designers, the enhancement of this quality by virtual learning environments is not sufficiently contrasted. In fact, the majority of works focus on assessing the quality of immersion and interaction with the environment, as well as the convenience of its use [18]. Aspects such as the promotion of imagination and creativity remain most of the time in the background, especially since they are difficult to be measured objectively [19].…”
Section: Introductionmentioning
confidence: 99%